2021
DOI: 10.3390/antibiotics10091043
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of RTD-1 in a Murine Model of Chronic Pseudomonas aeruginosa Lung Infection: Inhibition of NF-κB, Inflammasome Gene Expression, and Pro-IL-1β Biosynthesis

Abstract: Vicious cycles of chronic airway obstruction, lung infections with Pseudomonas aeruginosa, and neutrophil-dominated inflammation contribute to morbidity and mortality in cystic fibrosis (CF) patients. Rhesus theta defensin-1 (RTD-1) is an antimicrobial macrocyclic peptide with immunomodulatory properties. Our objective was to investigate the anti-inflammatory effect of RTD-1 in a murine model of chronic P. aeruginosa lung infection. Mice received nebulized RTD-1 daily for 6 days. Bacterial burden, leukocyte co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Monocytes/macrophages are the predominant cell type that secretes IL-1β. In pulmonary inflammatory diseases such as lung infection, 32 pulmonary fibrosis, 33 asthma, 34 and ALI, 35 a high number of IL-1β produced by AMs correlates strongly with disease severity. We found that iNOS and IL-1β mRNA and protein expression were extremely high in the LPS-treated AMs, and the knockdown of C/EBPβ significantly altered this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes/macrophages are the predominant cell type that secretes IL-1β. In pulmonary inflammatory diseases such as lung infection, 32 pulmonary fibrosis, 33 asthma, 34 and ALI, 35 a high number of IL-1β produced by AMs correlates strongly with disease severity. We found that iNOS and IL-1β mRNA and protein expression were extremely high in the LPS-treated AMs, and the knockdown of C/EBPβ significantly altered this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…When administered via nebulization in a CFTR F508delhomozygous murine model of chronic P. aeruginosa pulmonary infection, RTD-1 effectively decreased the lung infection burden. The in vivo antibacterial activity was coupled to a potent anti-inflammatory ability, which was exerted through the disruption of NF-κB signaling and the consequent inhibition of inflammasome formation [156]. The combination of the antimicrobial and anti-inflammatory properties of RTD-1 makes this compound a promising therapeutic approach for the treatment of CF lung infections [157].…”
Section: Natural Antimicrobial Peptidesmentioning
confidence: 99%